Abusive leadership: A moderated-mediation through leader-member exchange and by organizational politics - Drory, Amos; Shkoler, Or; Tziner, Aharon (Frontiers in Psychology, 2022)
Abusive leadership has been shown to have adverse consequences for both the employees and the organization. In the current paper, the impacts of such a leadership style on workers turnover intentions, counterproductive work behaviors and organizational citizenship behaviors are investigated through a dyadic lens – the mediation of leader-member exchange (LMX). Furthermore, when the workplace atmosphere is also tainted by internal organizational politics (as a moderator), these relationships deepen and and/or change (for the worse). To test the moderated-mediation research model, an online sample of 619 participants was obtained. The results support an interesting moderated mediation of LMX by organizational politics. Theoretical and practical implications, limitations and future research suggestions are discussed.